2014
DOI: 10.3892/ol.2014.2701
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-27a directly targets KRAS to inhibit cell proliferation in esophageal squamous cell carcinoma

Abstract: MicroRNAs (miRNAs) are a type of small non-coding RNA that negatively regulate gene expression levels by binding to the 3′-untranslated region of specific target mRNAs. To investigate the role of miR-27a in esophageal squamous cell carcinoma (ESCC), TargetScan software was used to predict the target gene of miR-27a. Kirsten rat sarcoma viral oncogene homolog (KRAS), which has been implicated as a regulator of cell proliferation, differentiation and transformation, was identified as a potential target gene of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 36 publications
3
24
0
Order By: Relevance
“…The genetic mutation of intracellular effectors that are involved in GTPase-related signaling pathways usually have an effect on the response of the targeted therapy [ 20 ]. Recently, KRAS mutations have been reported to be involved in human cancer, including nasopharyngeal carcinoma [ 21 ], ovarian cancer [ 22 ], lung cancer [ 23 ], pancreatic cancer [ 24 ], oral squamous cell carcinoma [ 25 ], esophageal squamous cell carcinoma [ 26 ], colorectal cancer [ 27 ], breast cancer [ 28 ] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…The genetic mutation of intracellular effectors that are involved in GTPase-related signaling pathways usually have an effect on the response of the targeted therapy [ 20 ]. Recently, KRAS mutations have been reported to be involved in human cancer, including nasopharyngeal carcinoma [ 21 ], ovarian cancer [ 22 ], lung cancer [ 23 ], pancreatic cancer [ 24 ], oral squamous cell carcinoma [ 25 ], esophageal squamous cell carcinoma [ 26 ], colorectal cancer [ 27 ], breast cancer [ 28 ] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…MiRNA are aberrantly expressed in various cancers and function as a novel class of oncogenes or tumor suppressor genes depending on their targets [ 26 ]. In ESCC, the aberrant expressions level of miRNAs, such as miR-27a, miR-9, miR-335, and miR-183, regulate tumor cell growth, apoptosis, migration, and invasion by targeting proteins involved in these cellular pathways [ 27 30 ]. Thus far, miRNAs that selectively regulate PLCE1 in ESCC have not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…miR-27a and miR-181a have several cancerous targeted genes. Recently it was reported that miR-27a, miR-181 targets the kras gene and deregulates its expression [40,41]. Mutations in TP53 and the KRAS gene are the most repeated molecular alterations related to GBC.…”
Section: Discussionmentioning
confidence: 99%